Socio-Religious Life of Kejawen Muslims in Badean Village, Bangsalsari District, Jember District - Zulaihah, Sitti; Nafisa Hasna Aulia; M. Maulana Husain (Journal of Islamic History, 2023)
This study examines the socio-religious life of Kejawen Muslims who are a minority amidst the majority of people who embrace puritan Islam in Badean village. The socio-religious life of Kejawen Muslims has different interpretations and religious practices from other Muslims. The approach used in this study is descriptive Qualitative with interviews and participant observation. This study reveals that Kejawen Muslims have a harmonious life with Puritan Muslims. They live side by side and respect each other. They even visit each other during religious holidays such as Eid al-Fitr, Eid al-Adha and the celebration of 1 Syuro. While the religious practices carried out by Kejawen Muslims refer to something unique. They combine Islamic teachings with Javanese cultural customs. Kejawen Muslims in Badean village use Javanese (krama Inggil) in reading prayers, prayers and praises before praying. Kejawen Muslims there also have their own way to determine Islamic holidays, such as Ramadan, Eid al-Fitr, Eid al-Adha. They use their own Javanese calendar, namely aboge (alip rebo wage).